Eco-friendly solar distillation apparatus for improving the yield of essential oils with enhancing organoleptic characteristics. (May 2022) - Nannaware, Ashween Deepak; Sai Kumar, Ch Mohan; Srivastava, Shubham; Singh, Suman; Gupta, Manglesh Kumar; Rout, Prasanta Kumar; Chanotiya, C.S.; Lal, R.K.; Nimdeo, Yogesh; Roy, Saumendu
Abstract: Solar-operated distillation unit (SDU) was designed and fabricated for extraction of valuable essentials from aromatic crops with a reduced cost of operation without carbon-credits to the environment. It comprised of distillation still, mesh grid frame, packed column, condenser, oil receiver, energy meter, resistive heating elements, and solar panels. This improved SDU can process 20 kg of aromatic crops in a batch type of operation. Resistive heating elements (4.5 kW) with controllers powered by the solar photovoltaic panel (5 kW) were used to produce the uniform steam generation within 20 min. This produced steam was adequate for continuous distillation (∼3 h) of aromatic crops to collect valuable essentials in an oil receiver. The total power consumed by the SDU in carrying out the distillation operation was calculated (13.5 kWh). The extraction studies of Ocimum cultivars (CIM-Shishir, 100 and 102) through SDU and Clevenger-type apparatus (standard set) revealed that the SDU process was yielded improved essential oil (0.36–0.73%). GC-FID and GC/MS analyses divulged that the essential oil obtained through SDU was superior in quality with improved percentage of biomarkers such as linalool (upto 62.8%) and methyl chavicol. Designed SDU has saved about 20 kg of wood per batch as compared to practiced wood-based distillation operation. Graphical abstract: Image 1